The effects of corporate social responsibility on manufacturing industry performance: the mediating role of social collaboration and green innovation - Handayani, Rini; Wahyudi, Sugeng; Suharnomo, Suharnomo (Business: Theory and Practice, 2017)
Manufacturing industry contributes to environmental pollution and social cost. Hence, corporate social responsibility (CSR) functions as a way to reduce the effects of corporate activities, to increase long-term performance and stakeholder trust. To increase its effectiveness, this study analyses the mediating role of green-oriented innovation and community participation in implementing the CSR. The study uses simple random sampling to collect 173 respondents from large scale manufacturing firms in Central Java, Indonesia. By using structural equation modeling, the findings showed the significant influence of CSR to the firm performance. The originality of this study concerns the need to involve social and environmental dimensions in applying the ethical program of CSR.